SISTEM INFORMASI KEHADIRAN SISWA MENGGUNAKAN QR KODE BERBASIS ANDROID: Studi Khasus SD NEGERI 105270 - Sitorus, Eliza Natalia; Jamaluddin, Jamaluddin; Harianja, Eva Julia G. (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2023)
This research develops a QR code-based student attendance information system at SD Negeri 105270. This system uses an Android application with a QR code for student attendance, aiming to increase the efficiency and accuracy of recording student attendance and improve the quality of education services. The research method includes application development using Android Studio and QR code integration. The teacher displays the QR code on their cell phone, and students scan the code using the attendance app on their cell phones. The results showed that this system speeds up the attendance process, reduces recording errors, and improves the security of student attendance data. This research provides a reference for other schools to implement a similar system with a QR code. It is hoped that this system can increase the efficiency and accuracy of student attendance as well as the quality of education services in schools.